Turkey : Seventh Review and Inflation Consultation Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses key findings of the Seventh Review and Inflation Consultation Under the Stand-By Arrangement for Turkey. Macroeconomic developments have become less favorable since the last review in May 2007. Political developments have distracted attention from an ambitious economic agenda. As a result, performance under the IMF-supported program suffered, with fiscal policy imparting an unplanned stimulus in 2007 and structural reforms meeting with delays. IMF staff welcomes the adoption of a medium-term fiscal framework to guide future policy, and encourages the authorities to strengthen its institutional underpinnings.